Teaching English to Young Learners: Qualities, Teaching Strategy and Classroom Management - qizi, Erkinova Aziza Erkin (International Journal of Formal Education, 2024)
In the Global World, the greater part of the Communication is done in English, as the vehicle of educating. As everybody realizes that it is Comprehensive or World Wide Language, where the current Globe is forging ahead by associating itself to others for doing their agreeable connections. In English Language Teaching (ELT), particularly, when English is associated with Class Room Teaching (CRT), it plays a major role in engrossing the student's consideration.